The Effectiveness of Learning Design in Increasing Motivation and Interest - Wahyuni, Sri; Asriani, Asni; Safitri, Riska; Kiramang, Khaeruddin (DIDAKTIKA, 2023)
This study aims to examine the effectiveness of instructional design in enhancing students' motivation and interest in learning at SMAN 28 Bone. The research was motivated by the crucial role of teachers as instructional designers in creating effective and efficient learning processes. A qualitative descriptive approach was employed, with data collected through observation, interviews, and documentation. The findings indicate that the instructional design at SMAN 28 Bone has been implemented fairly well through the development of modules and structured design stages. However, students’ learning motivation is still affected by external factors such as peer influence and inadequate learning facilities. Students tend to show greater interest when teachers apply strategies involving practice and hands-on activities, although the lack of instructional media remains a significant obstacle. Overall, the instructional design implemented at SMAN 28 Bone demonstrates potential to improve students’ motivation and interest in learning, but improvements are needed in terms of facilities and a more supportive learning environment.